Nurses’ Knowledge Regarding Cardiac Catheterization at General Hospital in Rania City - O. Sharif, Bayan; H. Salih, Shara; A. Sailh, Niga; I. Salim, Bahar (Kurdistan Journal of Applied Research, 2018)
Cardiac catheterization is a common word for a set of procedures that are implemented using this method, such as coronary angiography and left ventricle angiography. Coronary angiography is that invasive procedure which assumed as the golden standard for the diagnosis, estimation, and curing of heart diseases. There is a shortage of research of undergraduate students. The purpose of this descriptive cross-sectional study has been conducted to assess nurses’ knowledge regarding cardiac catheterization and associated factors at General Hospital in Rania city. Data were collected from a stability sample of 60 nurses using demographic form instead of the section with the conductive questionnaire of Knowledge regarding cardiac catheterization . The majority of study participants were female (81.7%) Therefore, 70% of nurses were married. About 43.3% of study participants were Academic nurse while (40%) of them were Institute nurse, however level of knowledge form institute graduated nurses has a highest level and the majority of participants were not trained (95%). Results acquired have shown that there is no sufficient knowledge of nurses regarding cardiac catheterization, among all levels of nurses and there is a significant relationship between most socio-demographic data in true question but there are opposite result for false questions. We therefore recommend the training course by ministry of health for nurses to improve the knowledge and health awareness regarding cardiac catheterization.